2019
DOI: 10.1186/s12931-019-1033-y
|View full text |Cite
|
Sign up to set email alerts
|

Altered irisin/BDNF axis parallels excessive daytime sleepiness in obstructive sleep apnea patients

Abstract: Study objectives Obstructive sleep apnea hypopnea syndrome (OSAHS) is a sleep-related breathing disorder, characterized by excessive daytime sleepiness (EDS), paralleled by intermittent collapse of the upper airway. EDS may be the symptom of OSAHS per se but may also be due to the alteration of central circadian regulation. Irisin is a putative myokine and has been shown to induce BDNF expression in several sites of the brain. BDNF is a key factor regulating photic entrainment and consequent circa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 78 publications
2
7
0
Order By: Relevance
“…Moreover, the level of both proteins was positively correlated with total sleep time (TST). Even though the effect sizes of these differences in our studies were low, they were in line with Kaminska et al and More et al, who showed a similar association between daytime sleepiness and BDNF overexpression in OSA [ 32 , 70 ]. In these studies, daytime sleepiness was evaluated by ESS.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the level of both proteins was positively correlated with total sleep time (TST). Even though the effect sizes of these differences in our studies were low, they were in line with Kaminska et al and More et al, who showed a similar association between daytime sleepiness and BDNF overexpression in OSA [ 32 , 70 ]. In these studies, daytime sleepiness was evaluated by ESS.…”
Section: Discussionsupporting
confidence: 92%
“…Then, it should be noticed that altered irisin/BDNF axis may be causative for circadian misalignment in OSA, and thus it might be suggested that excessive daytime sleepiness could be a result of the deterioration of circadian rhythm along with changes of serum irisin level [ 14 ]. Significant changes in ESS score, a simple questionnaire for patients' self-assessment of daytime sleepiness, were experienced if serum irisin level changed by 1 ng/mL, given the limited serum level of BDNF [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 10% weight gain gives rise to a 32% increase in the AHI; a 10% reduction yields a 26% improvement in OSA severity [ 13 ]. In addition, some investigators suppose that altered irisin/BDNF axis may be causative for circadian misalignment which leads to the excessive daytime sleepiness in OSA [ 14 ]. Moreover, notably some studies have also shown that serum irisin concentrations are still closely linked with the prevalence of OSA after getting rid of obesity interference by adjusting for BMI [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas elevated circulating irisin level was suggested to have role in the development of insuline resistance and atherosclerosis in patients with obstructive sleep apnea (32). Altogether, these data collectively suggest that diabetes and related CMD might, at least in part, be viewed as irisin-mediated disorders (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Irisinmentioning
confidence: 97%